A culture-sensitive taxonomy of response tokens: moving from listnership to speakership - Tsuchiya, Keiko (2010)
This thesis compares conversations between British tutors and British students, and conversations between British tutors and Japanese students, in English in order to investigate differences and similarities in their listenership behaviour in relation to the use of response tokens in the context of academic supervision sessions. A new method for conversation analysis to synthesise visual data with verbal data on timeline has been established. The concept of leadtime, which is a time scale to measure a distance between a point where a particular response token is uttered to a point where a turn transition occurs, has been introduced to implement the research method. Approaches in conversation analysis, roles of context, and intercultural communication are reviewed in this thesis. In addition, participants' assumptions of framing and turn-taking structure in conversation and self-expressions in listenership with reflection of their cultural values in interlanguage settings have been taken into consideration. The results from the preliminary research are summarised as follows: 1. Similarities in use of strategies for framework shifts, such as increase and decrease of response tokens before floor-taking, and multi-functional nature of hand gestures, such as hand gestures used for speaker change and metaphoric signs, have been recognised between the British-British conversations and the British-Japanese conversation. 2. L1 (first language) transfer has been observed in the Japanese students’use of response tokens, such as their constant use of head nods at a particular pace. These findings highlight areas for further research and application in intercultural communication.